Understanding the Relationships Between the Consumer Perception on Food Risks, Quality, and Safety Indicators of Braised Meat Sold in “Dibiterie” Restaurants in Dakar, Senegal - Orou Seko, Malik; Ossebi, Walter; Laré, Nibangue; Bonfoh, Bassirou (Frontiers in Veterinary Science, 2021)
Dibiteries are restaurants that sell braised meat of small ruminants and sometimes chicken. Current microbiological data indicate that the products sold are sometimes contaminated with pathogenic microorganisms exceeding the quality standards recommended for human consumption, hence a real public health concern. Despite the lack of hygiene, these establishments continue to thrive in the Senegalese food ecosystem. However, very few studies have analyzed the socio-economic motivations and risk representations of these populations who participate in the growing demand for meat from dibiteries. The main objective is to understand the relationships between consumer perception of food risks, quality, and safety indicators of braised meat sold in Dibiteries in Dakar. A total of 479 people from 404 households in the Dakar region were randomly selected and surveyed on the consumption of dibiterie meat using a structured questionnaire. The questionnaire allowed to measure the relative importance given by each interviewee to the indicators related to the risk of food infection, and the quality and safety of dibiterie meat. The structural equation model was used to design the paths and analyze the relationships. Of the 479 people interviewed, 291 people consumed dibiterie meat. Only 16% of consumers strongly perceive the quality and safety of meat. This strong perception has been positively associated with monthly food expenditure, while the age of consumers explained it negatively. Among the latent variables identified, the perceived price effect and the dibiteries' expertise were positively related to the perception on the safety and the perception on the nutritional quality of the product. The nutritional quality of the product had negatively impacted the risks of food infection perceived by consumers. The results of this study suggest the strengthening of hygiene standards in dibiteries and the awareness of consumers, especially young people, about the potential health risks associated with the consumption of dibiterie meat. Further work on willingness to pay to improve the safety of dibiterie meat is needed.